2013
DOI: 10.1177/105268461302300204
|View full text |Cite
|
Sign up to set email alerts
|

Defining and Activating the Role of Department Chair as Instructional Leader

Abstract: With strong connection to schoolwide policy and vision and to the realities of the daily life of teachers and students, the department chair is uniquely positioned to play an important role in advancing instructional effectiveness (Printy, 2008; Weller, 2001). This article provides an in-depth look at the efforts of three urban comprehensive high schools to revision the role of department chair as instructional leader. The case studies identify building a shared vision, trust, role clarity, professional develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Recent research has emphasized the effect of instructional leadership on the overall progress of education (Bendikson et al, 2012; Hallinger, 2003; Hallinger and Lee, 2013; Robinson, 2008). HoDs have exceptional positions as catalysts for curriculum and instruction within their own departments, and they can foster ideas for school improvement over the more extensive school setting (Busher and Harris, 1999; Daresh and Male, 2001; Kelley and Salisbury, 2013; Kleine-Kracht, 1993).…”
Section: Conceptual Background and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has emphasized the effect of instructional leadership on the overall progress of education (Bendikson et al, 2012; Hallinger, 2003; Hallinger and Lee, 2013; Robinson, 2008). HoDs have exceptional positions as catalysts for curriculum and instruction within their own departments, and they can foster ideas for school improvement over the more extensive school setting (Busher and Harris, 1999; Daresh and Male, 2001; Kelley and Salisbury, 2013; Kleine-Kracht, 1993).…”
Section: Conceptual Background and Hypothesesmentioning
confidence: 99%
“…Internationally, HoDs’ roles vary in terms of adapting instructional leadership practices to foster teachers’ professional learning as contributors to cultural and educational context (Kelley and Salisbury, 2013; Tan, 2012). Studies of instructional leadership practices have revealed that HoDs are critical for facilitating teachers’ engagement, cooperation, and school initiatives in their departments (Busher and Harris, 1999; Dinham, 2005; Jaca, 2013; Kelley and Salisbury, 2013). Ghamrawi (2010) showed that subject leaders can foster instructional leadership and promote a collegial community for developing the quality of teaching and learning.…”
Section: Conceptual Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that shared leadership does not necessarily favor instructional leadership or transformational leadership. However, there is a growing body of research related to shared or distributed instructional leadership (see, e.g., Bredeson, 2013; Kelley & Salisbury, 2013; Klar, 2013; Marks & Printy, 2003).…”
Section: Selecting An Appropriate Feedback Instrumentmentioning
confidence: 99%
“…The study reported in this article is part of a larger study of the leadership-for-learning project (see, e.g., Kelley & Salisbury, 2013;Klar, 2013). This article focuses on the professional development practices that support the emergence of distributed instructional leadership (DIL) in six urban high schools.…”
mentioning
confidence: 99%